Analyzing electronic poetry - Di Rosario, Giovanna (Primerjalna književnost, 2013)
This paper aims to show the different textualities put forward by electronic poetry. In order to explain how poetic language can create different textualities due to the interaction of different media, three close-readings of electronic poems will be offered.
Keywords: digitalna književnost; novi mediji; elektronska poezija; tekstualnost